2020
DOI: 10.5194/nhess-20-2379-2020
|View full text |Cite
|
Sign up to set email alerts
|

A spaceborne SAR-based procedure to support the detection of landslides

Abstract: Abstract. The increasing availability of free-access satellite data represents a relevant opportunity for the analysis and assessment of natural hazards. The systematic acquisition of spaceborne imagery allows for monitoring areas prone to geohydrological disasters, providing relevant information for risk evaluation and management. In cases of major landslide events, for example, spaceborne radar data can provide an effective solution for the detection of slope failures, even in cases with persistent cloud cov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 51 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Our model outcomes also corroborate the preferential location of storm-triggered landslides at the toe of hillslopes (Meunier et al, 2008). As a long-term insight, we believe that a better characterisation of the timing of landslide failure during large storms or typhoons, for instance thanks to the development of SAR imagery (Singhroy and Molch, 2004;Xu et al, 2019;Esposito et al, 2020), could help to separate the respective role of atmospheric pressure drop and rainfall in slope destabilisation. Geol.,197,[172][173][174][175][176][177][178][179][180][181][182][183][184][185][186][187]…”
Section: Discussionsupporting
confidence: 75%
“…Our model outcomes also corroborate the preferential location of storm-triggered landslides at the toe of hillslopes (Meunier et al, 2008). As a long-term insight, we believe that a better characterisation of the timing of landslide failure during large storms or typhoons, for instance thanks to the development of SAR imagery (Singhroy and Molch, 2004;Xu et al, 2019;Esposito et al, 2020), could help to separate the respective role of atmospheric pressure drop and rainfall in slope destabilisation. Geol.,197,[172][173][174][175][176][177][178][179][180][181][182][183][184][185][186][187]…”
Section: Discussionsupporting
confidence: 75%
“…This could be a serious problem for some cases as it might take many days for the clouds to clear the sky. Methods working on spaceborne Synthetic Aperture Radar data can provide information even through cloud cover and should be used for such situations 38 , 39 . All the study areas selected for this study had had high coverage of vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have demonstrated that all three of these backscatter coefficients can be applied to detect vegetation removal due to landslides and other processes such as deforestation and wildfires (e.g. Ban et al, 2020;Belenguer-Plomer et al, 2019;Bouvet et al, 2018;Esposito et al, 2020;Hernandez et al, 2021;Mondini, 2017;Mondini et al, 2019;Motohka et al, 2014). Here we used γ 0 .…”
Section: Theory: Sar Backscatter and Landslidesmentioning
confidence: 99%